GUILD PAKAN KOMUNITAS BURUNG DI KEBUN RAYA LIWA KABUPATEN LAMPUNG BARAT - Abdurrahman Rofiq; Sugeng Prayitno Harianto; Dian Iswandaru; Gunardi Djoko Winarno (Jurnal Belantara, 2021)
The vegetation on Liwa Botanical Gardens is used by several types of birds as a place of rest, sleep, nest and forage. This study was purposely done to classify bird species based on feed group / guild type. The method used in this research is point count. The bird species data obtained were grouped based on the feed guild which was divided into 6 types of guilds including, insectivoree, carnivoree, frugivore, granivoreee, nectarivoreous, and omnivoree. Each species only have one guild type, as many as 41 species of birds were found in Liwa Botanical Gardens, which was dominated by frugivores.